Analisis kemampuan pemecahan masalah matematika siswa dalam menyelesaikan soal cerita ditinjau dari gaya kognitif impulsif pada masa pandemi covid-19 - Muniroh, Lisa; Sugiyanti, Sugiyanti; Nursyahidah, Farida (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Mathematical problem solving is a process carried out to find solutions to problems. The purpose of this study was to analyze students ’problem solving abilities in solving story problems based on students’ impulsive cognitive styles during the covid-19 pandemic. This research is a study that uses a qualitative research paradigm. The subjects of this study were 7H grade students of SMP N 1 Karangrayung. Determination of the subject is done by MFFT (Matching Familiar Figure Test). Data collection techniques in this study used written data on mathematical problem solving tests and interviews with each subject. The problem solving tests are adjusted to Polya’s problem solving indicators, namely understanding the problem, planning the solution, implementing the solution, and checking again. In completing problem solving tests, impulsive subjects are able to solve problems coherently, but the subject does not pay attention to the relationships between interrelated questions. Impulsive subjects do not re-examine answers to problem solving tests, and tend to be less careful about solving problems.